Phytoplankton and Ecological status of natural lakes in Greece (2023)
Nikolopoulou, I., V. Navrozidou, K. Moschandreou, D. Kemitzoglou, and V. Tsiaoussi. 2023. Phytoplankton and Ecological status of natural lakes in Greece. Poster presentation in Eighth European Phycological Congress-EPC8 "Scientific Opportunities for a Global Algal Revolution", Brest, Brittany, France, 20-26 August 2023.